PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASI SEBAGAI PEMEDIASI PADA DINAS CIPTA KARYA PROVINSI ACEH - Sarah Tiara, Amri (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
ABSTRACTThis study aims to measure the Effect of Organizational Commitment as the mediator of Job Satisfaction with Turnover Intention Contract Workers at Dinas Cipta Karya of Aceh Province. The sample used in this research is the contract employee at Dinas Cipta Karya Provinsi Aceh, which is 150 respondents. The data collection equipment used in this research is questionnaire. The sampling technique used is Totally sampling. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved. The results showed: 1) Job Satisfaction has an effect on to Contract Worker's Satisfaction at Dinas Cipta Karya Provinsi Aceh. 2) Job satisfaction affects the commitment of Contractor Workers Organization at Dinas Cipta Karya of Aceh Province. 3) Organizational Commitment has an effect on Turnover intention in Dinas Cipta Karya Provinsi Aceh. 4) Organizational Commitment mediates the influence of Job Satisfaction on Turnover Intention of Contract Workers at Dinas Cipta Karya of Aceh Province. Keywords: Organizational Commitment, Job Satisfaction and Turnover Intention.